2022
DOI: 10.14202/vetworld.2022.1699-1705
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ehrlichia-, Babesia-, and Hepatozoon-infected brown dog ticks in Khon Kaen Province, Northeast Thailand

Abstract: Background and Aim: The brown dog tick, Rhipicephalus sanguineus sensu lato, is the most common tick found on domestic dogs in Southeast Asia, including Thailand. Canine tick-borne pathogens are a public health concern worldwide. Tick-borne diseases are diagnosed by identifying pathogens based on the morphological or molecular analyses of dog blood samples. However, the collection of ticks, a non-invasive procedure, is easier than drawing blood. This study aimed to demonstrate the usefulness of collecting brow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(51 reference statements)
0
1
0
1
Order By: Relevance
“…The study in Northeast Thailand showed the high prevalence of H. canis (65.71%), followed by Babesia spp. (31.43%) and E. canis (30.0%), in brown dog ticks from infected dogs ( 25 ). In contrast, another research in same area found that E. canis is the most single pathogen in dogs (64.0%) and ticks (82.0%) ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study in Northeast Thailand showed the high prevalence of H. canis (65.71%), followed by Babesia spp. (31.43%) and E. canis (30.0%), in brown dog ticks from infected dogs ( 25 ). In contrast, another research in same area found that E. canis is the most single pathogen in dogs (64.0%) and ticks (82.0%) ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…7-N° 2, 2023, pp. 1188-1200 Journal Scientific MQRInvestigar 1197 (Eamudomkarn et al, 2022). En nuestro estudio el 77,77 % (14/18) de pacientes con resultado positivo a Ehrlichia canis en la cPCR tuvieron presencia de garrapatas al momento de la consulta, si bien no se evaluaron directamente las garrapatas Rhipicephalus sanguineus hay que considerar que estos ectoparásitos albergan múltiples patógenos que afectan a humanos y caninos.…”
Section: Discussionunclassified